Assessing the impact of dual alcohol blends on diesel engine performance and exhaust emissions / Muhammad Fairuz Remeli, Muhammad Aiman Hakim Haron and Baljit Singh - Remeli, Muhammad Fairuz; Haron, Muhammad Aiman Hakim; Singh, Baljit (Smart Manufacturing Research Institute (SMRI), 2024)
The increasing reliance on diesel fuel has heightened concerns about depleting fossil fuel reserves and environmental impacts. In response, researchers are exploring alternative fuel options, such as blends of alcohol and diesel, to improve sustainability. This study investigates the performance and emissions characteristics of several ethanol, methanol, and diethyl ether (DEE) blends with biodiesel and diesel. The tested fuel blends include B10 (90% diesel, 10% biodiesel), BDE (75% diesel, 10% biodiesel, 15% ethanol), BDE2DEE (75% diesel, 10% biodiesel, 15% ethanol, 2% DEE), BDE5DEE (75% diesel, 10% biodiesel, 15% ethanol, 5% DEE), and MBD2DEE (75% diesel, 10% biodiesel, 15% methanol, 2% DEE). Engine performance was evaluated in terms of brake-specific fuel consumption (BSFC), brake power, exhaust gas temperature, and mass and volume flow rates at varying engine loads. The results demonstrate that fuel blends with diethyl ether, particularly BDE5DEE, exhibited superior performance in reducing emissions. NOx emissions decreased by up to 16.2%, while CO2 emissions were reduced by 15.0%. Additionally, blends with diethyl ether lowered brake-specific fuel consumption by 30.7% compared to standard diesel (B10). The blend MBD2DEE, which includes methanol, delivered the highest brake power at higher loads (75%), peaking at 2.91 kW, indicating its strong potential for high-load applications. These findings suggest that dual alcohol-diesel blends, especially those containing diethyl ethers, offer a promising route for improving fuel efficiency and reducing harmful emissions, making them viable alternatives to traditional diesel fuel.